Modelování úmrtnosti pro potřeby důchodového zabezpečení - Pacáková, Viera; Mudrochová, Jana (Univerzita Pardubice, 2010)
As a result of longevity risk is the reform of the pension systems in many countries. It is also necessary to estimate the mortality laws of elderly persons and the future changes in the area of mortality, for example on the basis of extrapolation of the trends observed. The article describes and presents application of the method of Gompetz-Makeham graduation of the observed mortality data.
Keywords: mortality; mortality rate; longevity; pension system; Gompertz-Makeham law